The effect of biomechanical variables on the assessment of vaulting in top-level artistic female gymnasts in world cup competitions - Farana, R.; Vaverka, F. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2012)
A vaulting performance takes a short time and it is influenced by and affects the quantity of mechanical variables. After the 2000 Olympic Games, the traditional horse was replaced by a new vaulting table. While the biomechanical data of vaulting using the new table (post 2000 Olympic competition) are not available yet, there is a question what the current technique of handspring performed by top-level female gymnasts looks like. OBJECTIVE: The aim of the study is to determine the biomechanical factors that govern success in the performance of the handspring and front somersault vaults. METHODS: Eight top-level female gymnasts participated in this study. For the 3D spatial movement analysis, two digital camcorders with a frame rate of 50 fields per second were used. The data was digitized by the Simi motion software. The method of Hay and Reid (1988) was used to identify the biomechanical variables that determine the linear and angular motions of the handspring and front somersault vaults. A correlation analysis was used to establish the strength of the relationship between the causal biomechanical variables and the judges' scores. The level of statistical significance was determined at the value of p RESULTS: Five out of 23 examined variables showed significant correlations with the scores. A significant correlation was found in the vertical height of the body center of mass during the take-off from the vaulting table (r = 0.86), in the maximum height of the body center of mass in the second flight phase (r = 0.83), in the change of the horizontal velocity during the phase of the take-off from the vaulting table (r = -0.69), in the horizontal component of the velocity during the spring from the vaulting table (r = 0.75) and in the duration of the second flight phase (r = 0.69). CONCLUSIONS: The phase of the take-off from the vaulting table is a crucial phase of the vault. Top-level artistic female gymnasts are able to execute the take-off from the vaulting table in a relatively short period of time with a full extent of the movement (maximization of the height of the body center of mass at the board take-off). The take-off from the vaulting table is executed at a high vertical and horizontal velocity that ensures a sufficient height of the vault and landing distance of from the vaulting table. The longer time of the second flight allowed gymnasts to complete the rotation motion during the second flight phase and perform a controlled and safe landing.